How, when and why abilities go social: researching children’s empathy and prosocial behaviors in context - Roerig, Simone; van Wesel, Floryt; Evers, Sandra J. T. M.; van der Meulen, Anna; Krabbendam, Lydia (Frontiers in Psychology, 2023)
The current paper undertakes interdisciplinary research on empathy in children by combining insights and methodological tools from the fields of psychology, education and anthropology. The researchers aim to map how children’s individual empathic abilities studied on a cognitive level do or do not coincide with their empathic expressions as part of group dynamics in daily life at the classroom level. We combined qualitative and quantitative methods within three different classrooms at three different schools. In total, 77 children aged between 9 to 12 years participated. The results indicate how such an interdisciplinary approach can provide unique insights. Through the integration of data from our different research tools we could reveal the interplay between different levels. More specifically this meant showing the possible influence of rule-based prosocial behaviours versus empathy based prosocial behaviours, the interplay between community empathic abilities and individual empathic abilities, and the role of peer culture and school culture. These insights can be seen as encouragement towards a research approach that extends beyond the single disciplinary field in social science research..